Fishing gear productivity related fishing intensity and potency of stock vulnerability in Sunda strait. (January 2020) - Yonvitner,; Yuliana, E; Yani, D E; Setijorini, L E; Nurhasanah,; Santoso, A; Boer, M; Kurnia, R; Akmal, S G
Abstract: Increasing of fishing productivity is an indicator of fishing intensity. The increasing productivity dominated by a small and immature population also as an indicator of vulnerability stock in the sea. Therefore, fishing productivity research is important as the basis of the study of the efficiency and vulnerability of fish stocks. This research was conducted in the Sunda strait using landing fish data in Labuan Landing Port from February until July 2018. Evaluation of the effectivity and intensity of fishing pressure was determined by a descriptive statistic from average and deviation of the fishing number. The results of the research showed that the productivity of purse seine, beach seine, mini purse seine, mini trawl higher than that of other gears. The average productivity value purse seine, beach seine, mini purse seine, mini trawl was 100.63, 84.16, 25.5 and 31. 6 kg per unit per trip, respectively. These gears were more effective compared to other fishing gears. These results can be used as an indicator and basis to evaluate the vulnerability stock from fishing activity.